Case series: Chemical pneumonitis caused by exposure of sodium ibandronate powder - Pan, Ting; Ma, Guofeng; Qian, Jiali (Frontiers in Public Health, 2025)
This report presents two cases of chemical pneumonitis caused by the exposure of sodium ibandronate powder, a bisphosphonate used for treating osteoporosis. They are both pharmaceutical workers, and they inhaled the powder after an accidental spill in the lab. They developed similar symptoms, but different imaging features, only one showed fibrotic changes. After the blood test and bronchoscopy examination, they both diagnosed as chemical pneumonitis. Their symptoms improved after treatment with glucocorticoids. Their lung lesions resolved completely after continued treatment. The findings suggest that the importance of appropriate safety measures in environments where pharmaceutical powders may be handled, such as in the pharmaceutical industry. Chemical pneumonitis from inhaled sodium ibandronate can have varying CT appearances and may benefit from glucocorticoids therapy.